Rancang Bangun Sistem Kontrol Irigasi Otomatis Berbasis IoT untuk Tanaman Stevia - Budy Gunawan; Arbi Alfian Mas’ud; Khasanul Khakim; Muhammad Febriyanda Wiryawan; Reza Rachmat Setyabudi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research focuses on developing an IoT-based automatic irrigation control system for stevia plants to optimize plant growth and water usage efficiency. The system integrates ESP32 microcontroller with soil moisture sensors, DS18B20 temperature sensors, and DHT11 environmental sensors for comprehensive monitoring. Using Research and Development (R&D) methodology with an experimental approach, the system was designed and implemented to automatically control irrigation based on soil moisture levels. The results demonstrate that the system successfully maintains optimal soil moisture by activating the pump when moisture levels fall below 38% and deactivating it above 40%. Real-time monitoring through the Blynk platform enables remote observation and control of environmental parameters. The integration of multiple sensors with IoT technology provides an efficient solution for stevia plant irrigation management, offering potential applications in smart agriculture.